Development Projects as Policy Experiments: An Adaptive Approach to De velopment Administration - Rondinelli, Dennis A. (Methuen, 1983)
International assistance programmes for developing countries are in ur gent need of revision. Continuous testing and verification is required if development activity is to cope effectively with the uncertainty a nd complexity of the development process. This examines the alternativ es and offers an approach which focuses on strategic planning, adminis trative procedures that facilitate innovation, responsiveness and expe rimentation, and on decision-making processes that join learning with action. A useful text for academics and practitioners in development s tudies, geography and sociology.